ChemInform Abstract: A Brief Introduction to the Development of Biogenic Synthesis of Metal Nanoparticles. Issue 41 (October 2015) - Mondal, Samiran; Basu, Saswati; Begum, Naznin Ara; Mandal, Debabrata
Abstract Review: 70 refs.